A novel insertion from chromosome 18 to chromosome 15 with a 183Kb 18q deletion - Pinto Leite, Rosário (2018)
Chromosome 18q- syndrome is a rare chromosomal disorder with an incidence of 1 in 40 000 live births. The phenotype is highly variable, depending on the amount of deleted genetic material, and is characterized by mental retardation, developmental delay, hypotonia, seizures, obesity, abnormal behavior, short stature and craniofacial dysmorphisms. We report a patient with mental retardation, dysmorphic features, hypotonia, growth retardation, severe expressive speech delay and Duane syndrome, with an insertion of 18q in 15q causing a 183Kb deletion in18q. Cytogenetic and SNP array analysis showed a female karyotype presenting a de novo rare chromosome rearrangement: an insertion of the 18q21q23 on the 15q22 region, with deletion 18q12.3 (chr18:42,484,980-42,667,966, [GRCh37]), involving only the MIR4319 and SETBP1 genes. There are few reports of 18q12.3 deletion associated with mild dysmorphic features, mental retardation and impairment of expressive language. To our knowledge this is the smallest deletion described, involving two genes: SETBP1 and a microRNA (MIR4319). SETBP1 gene is associated to expressive speech delay. The authors present a literature review of 18q12.3 deletion.